1999
DOI: 10.1017/s0048577299981003
|View full text |Cite
|
Sign up to set email alerts
|

Impedance pneumography: Noise as signal in impedance cardiography

Abstract: Thoracic impedance is modulated by events within the respiratory cycle, which represents a source of "noise" in impedance cardiography. Respiration itself, however, is a physiological rhythm of interest to psychophysiologists. We report here methods and validation for deriving impedance pneumographic measures of respiration from impedance cardiography signals, based on standard tetrapolar band electrodes. We recorded the change in impedance (delta Z), the first derivative of the change in impedance (dZ/dt), ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 16 publications
3
109
0
Order By: Relevance
“…The respiratory signal was derived from the raw data of thoracic impedance (Ernst et al, 1999;Houtveen et al, 2006). In addition to the breathing rate (cycles per minute), the proportion of regular breathing cycles were computed.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…The respiratory signal was derived from the raw data of thoracic impedance (Ernst et al, 1999;Houtveen et al, 2006). In addition to the breathing rate (cycles per minute), the proportion of regular breathing cycles were computed.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…signal. Recent studies from different groups~Ernst, Litvack, Lozano, Cacioppo, & Berntson, 1999;de Geus, Willemsen, Klaver, & van Doornen, 1995! have shown that, after appropriate bandpass filtering, thoracic impedance can be used to obtain a reliable index of respiratory frequency.…”
Section: Baro-reflex and Pulmonary Stretch-reflexmentioning
confidence: 99%
“…have shown that, after appropriate bandpass filtering, thoracic impedance can be used to obtain a reliable index of respiratory frequency. Furthermore, in a within-subject design, the spectral power of the filtered thoracic impedance signal can be used as an approximation of changes in respiratory depth Ernst et al, 1999!.…”
Section: Baro-reflex and Pulmonary Stretch-reflexmentioning
confidence: 99%
“…de Geus et al (1995) showed that band-pass filtered thoracic impedance signals obtained from four spot electrodes can reliable be used for the assessment of respiratory rate. Ernst et al (1999) took this further and validated the full respiratory signal, as obtained from impedance cardiography, against respiratory signals obtained in parallel from a respiratory belt and continuous direct spirometry. Validation was done during baseline, paced breathing, abdominal and thoracic breathing and a verbal arithmetic task.…”
Section: Introductionmentioning
confidence: 99%
“…This approach requires both signals to be equally scaled and cannot be applied to demonstrate a deviation between the unscaled thoracic impedance amplitude and spirometric volume. To deal with this problem, Ernst et al (1999) computed variability of gain parameters (referred to in their paper as Fconsistency of gain_). Gains can be obtained by dividing the observed thoracic impedance amplitudes (the output values) by the corresponding spirometric volumes (the input values).…”
Section: Introductionmentioning
confidence: 99%